EVIDENCE OF MONTHLY ANOMALIES IN PAKISTAN STOCK EXCHANGE - Shamshir, Musarrat; Baig, Jawwad Mirza; Mustafa, khalid (Archives of Business Research, 2016)
The study is an extended effort to investigate the monthly anomalies across Pakistani stock market, on four stock indices of Pakistan stock exchange by using the data from previously known as Karachi stock exchange for the period from January 01, 2009 to August 31, 2014. The study is a unique attempt of its kind to include all four indices for exploring turn-of-the-month and month-of-the-year effects with special consideration of tax-loss-selling hypothesis for the month of July for conventional January effect. Evidences of turn-of-the-month effect were found in indices except for KSE-30 and KMI-30 index. The study also found significant January returns evident in all four indices; however the effect cannot be contributed to tax-loss-selling hypothesis. Optimistic attitudes towards the year ahead and liquidity preference seem to be related with the heavy buying. July effect is found to exist in the market which may be contributed to tax-loss-selling hypothesis. Although, KSE-30 and KMI-30 indices were found to demonstrate atypical results as compared to the rest of the indices, yet it is concluded that stock market of Pakistan is not devoid of monthly anomalies.